A novel duplex ddPCR assay for the diagnosis of schistosomiasis japonica: proof of concept in an experimental mouse model. Issue 8 (9th March 2017) - WEERAKOON, KOSALA G.; GORDON, CATHERINE A.; CAI, PENGFEI; GOBERT, GEOFFREY N.; DUKE, MARY; WILLIAMS, GAIL M.; MCMANUS, DONALD P.
SUMMARY: The current World Health Organization strategic plan targets the elimination of schistosomiasis as a public health problem by 2025 and accurate diagnostics will play a pivotal role in achieving this goal. DNA-based detection methods provide a viable alternative to some of the commonly used tests, notably microscopy and serology, for the diagnosis of schistosomiasis. The detection of parasite cell-free DNA in different clinical samples is a recent valuable advance, which provides significant benefits for accurate disease diagnosis. Here we validated a novel duplex droplet digital PCR assay for the diagnosis of Chinese (SjC) and Philippine (SjP) strains of Schistosoma japonicum infection in a mouse model. The assay proved applicable for both SjC and SjP infections and capable of detecting infection at a very early intra-mammalian stage in conveniently obtainable samples (urine and saliva) as well as in serum and feces. The target DNA copy numbers obtained in the assay showed a positive correlation with the infection burden assessed by direct traditional parasitology. The potential to detect parasite DNA in urine and saliva has important practical implications for large-scale epidemiological screening programmes in the future, particularly in terms of logistical convenience, and the assay has the potential to be a valuable additional tool for the diagnosis of schistosomiasis japonica.